2017
DOI: 10.1097/pcc.0000000000001030
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Venovenous Hemofiltration in Children Less Than or Equal to 10 kg: A Single-Center Experience

Abstract: We have shown that continuous venovenous hemofiltration can be performed with good outcomes in children less than or equal to 10 kg using relatively high blood flow rates and with the current equipment available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Percentage fluid overload was calculated using the following formula: [(Total Fluid Intake in Liters − Total Fluid Output in Liters) / Admission Weight in Kilograms] × 100. This equation was based on the literature …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Percentage fluid overload was calculated using the following formula: [(Total Fluid Intake in Liters − Total Fluid Output in Liters) / Admission Weight in Kilograms] × 100. This equation was based on the literature …”
Section: Resultsmentioning
confidence: 99%
“…Shown is the association with mortality, stratified by case mix. Included were 22 studies . ALI indicates acute lung injury; CRRT, continuous renal replacement therapy; %FO, percentage fluid overload; and OR, odds ratio.…”
Section: Resultsmentioning
confidence: 99%
“…The neck veins are preferred sites for patients weighing less than 5 kg [ 14 ]. In the studies of Kaempfen et al [ 13 ] and Symons et al [ 10 ], the most frequently used catheter sites were the femoral vein in CRRT studies performed in children weighing less than or equal to 10 kg. Unlike their results, in this multicenter study, we observed that the RJVI was the most used site for vascular access.…”
Section: Discussionmentioning
confidence: 99%
“…(VIS = dopamine dose [μg/kg/min] + dobutamine dose [μg/kg/min] + 100 × epinephrine dose [μg/kg/min] + 10 × milrinone dose [μg/kg/min] + 10,000 × vasopressin dose [U/kg/min] + 100 × norepinephrine dose [μg/kg/min]) [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Medications, transfusions, and total parenteral nutrition (TPN) also significantly increase the daily fluid intake. Previous studies have shown that FO is associated with worse outcomes in children [9][10][11][12][13][14]. In a study of HCT recipients with acute kidney injury (AKI), Michael et al [9] found increased mortality among patients with >10% FO compared with those with <10% FO.…”
Section: Q1 How Should Fluid Status Be Managed In Children Undergoinmentioning
confidence: 99%